1997
DOI: 10.1063/1.474605
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics of H-bonded liquids confined in porous silica gels by Rayleigh wing spectroscopy

Abstract: Reorientational dynamics of neat liquid propylene glycol molecules is compared with that of confined molecules in 25 and 75 Å pores of a sol-gel porous glass by means of depolarized light-scattering spectroscopy. The experimental spectra, performed as a function of temperature, show unambiguously the slowing down of the collective reorientational processes triggered by the confinement effects. Such results confirm the main role played by the strong dipolar interactions on the dynamics of hydrogen-bonded liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The two glass-forming liquids addressed below, propylene glycol and glycerol, have both been subject to dielectric investigations in confined spaces. For PG, an increase of the relaxation time and ͑equivalently͒ glass transition temperature T g has been reported in a number of studies, 43,45,53,65,66 consistent with our solvation result in 4 nm Vycor glass. Only one study reports the reverse effect of faster dynamics upon hard confinement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The two glass-forming liquids addressed below, propylene glycol and glycerol, have both been subject to dielectric investigations in confined spaces. For PG, an increase of the relaxation time and ͑equivalently͒ glass transition temperature T g has been reported in a number of studies, 43,45,53,65,66 consistent with our solvation result in 4 nm Vycor glass. Only one study reports the reverse effect of faster dynamics upon hard confinement.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental approaches to the behavior of confined and interfacial liquids have used very different techniques, [3][4][5]7,[43][44][45][46][47][48] confining geometries, 2,49-52 and surface properties 8,22,53 . An attempt to sort the various experimental approaches to confined liquids by the confinement type is shown in Table II, which disregards surface treatments as an additional experimental variable.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Generally speaking, two competing effects seem to play the main role in modifying the dynamics of confined water with respect to the bulk state: the interaction forces with the substrate molecules (chemical traps), and the bare geometrical confinement (physical traps), i.e., the excluded volume effect. The separation of these two contributions, whose interplay is strongly dependent on the particle density and the size of the confining system, is still a problem that has not been completely solved yet.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be prepared as high-optical-quality monoliths that have a narrow distribution of pore sizes centered about a controllable average size, and as such are conducive to studies by numerous physical techniques. [9][10][11][12][13][14][15][16][17] In a number of previous studies [18][19][20] we have employed optical Kerr effect 21,22 ͑OKE͒ spectroscopy to study the dynamics of liquids confined in these materials. These experiments demonstrated that OKE spectroscopy is a powerful means of obtaining molecular-level information about the structure and dynamics of liquids confined in nanoporous glasses.…”
Section: Introductionmentioning
confidence: 99%